2015
DOI: 10.1002/jcc.24197
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the optical properties of naphthalenediimides: A frontier orbital analysis across the periodic table

Abstract: A comprehensive theoretical treatment is presented for the electronic excitation spectra of ca. 50 different mono-, di-, and tetrasubstituted naphthalenediimides (NDI) using time-dependent density functional theory (TDDFT) at ZORA-CAM-B3LYP/TZ2P//ZORA-BP86/TZ2P with COSMO for simulating the effect of dichloromethane (DCM) solution. The substituents -XHn are from groups 14-17 and rows 2-5 of the periodic table. The lowest dipole-allowed singlet excitation (S0 -S1 ) of the monosubstituted NDIs can be tuned from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Introducing a π‐donating NH 2 (X in Scheme ) substituent on the benzene ring (D2) increases its HOMO energy (C 6 H 4π,HOMO ), whereas a π‐accepting CN (Y in Scheme ) substituent (A2) lowers its LUMO energy (C 6 H 4π*,LUMO ), resulting in both cases in a decrease of Δ E frag H‐L (Fig. b) in qualitative agreement with recent studies . The HOMO arises from the antibonding combination of the occupied D1 π,HOMO and NH 2π,HOMO fragment orbitals, whereas the LUMO originates from the bonding combination of the unoccupied A1 π*,LUMO and CN π*, LUMO fragment orbitals.…”
Section: Resultssupporting
confidence: 89%
“…Introducing a π‐donating NH 2 (X in Scheme ) substituent on the benzene ring (D2) increases its HOMO energy (C 6 H 4π,HOMO ), whereas a π‐accepting CN (Y in Scheme ) substituent (A2) lowers its LUMO energy (C 6 H 4π*,LUMO ), resulting in both cases in a decrease of Δ E frag H‐L (Fig. b) in qualitative agreement with recent studies . The HOMO arises from the antibonding combination of the occupied D1 π,HOMO and NH 2π,HOMO fragment orbitals, whereas the LUMO originates from the bonding combination of the unoccupied A1 π*,LUMO and CN π*, LUMO fragment orbitals.…”
Section: Resultssupporting
confidence: 89%
“…All the equilibrium geometries were verified by vibrational analyses to be (local) minimum energy structures (zero imaginary frequencies). The frontier orbital wavefunctions exhibit a nodal plane at the two nitrogen positions in the diimide ring, which suggests that the alkyl or phenyl groups at these positions would have no significant impact on the molecular electronic properties . We found exactly the same observation.…”
Section: Computational Detailssupporting
confidence: 74%
“…In this paper we present a systematic TDDFT study of core‐substituted naphthalene diimides (cNDIs) which are well known for their tunable absorption and emission properties, ranging over the entire visible to near‐infrared spectrum . The parent NDI molecule has been extensively used as an electron acceptor exhibiting a high π‐acidity, as well as for electron transport and photoinduced CT applications .…”
Section: Introductionmentioning
confidence: 99%
“…This way of substitution is found to be most common in the literature. 21 , 25 , 28 , 54 Using CAT, a total of 1015 NDI derivatives are generated: 7 mono-substituted, 28 di-substituted, 343 tri-substituted, and 637 tetra-substituted derivatives. The molecule sizes vary from 33 to 106 atoms.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that electron-donating functional groups like alkoxy, 25 , 26 alkylamino, 26 alkylthio, 25 and thiophenes 27 affect optical properties via electronic effects (mainly mesomeric and inductive) on the frontier molecular orbitals, causing a decrease of the HOMO/LUMO gap while increasing the HOMO and LUMO energies. 28 , 29 The lowest transition in NDI is susceptible to the substituent effect, while the higher transition is unaltered and resembles the properties of non-substituted NDI. 21 , 25 …”
Section: Introductionmentioning
confidence: 98%